Characterization of helical APPLE X undulators with 90 mm period for the European XFEL. Issue 1 (1st December 2022) - Yakopov, M.; Calvi, M.; Casalbuoni, S.; Englisch, U.; Karabekyan, S.; Liang, X.; Schmidt, T.
Abstract: European XFEL is going to provide full polarization control in the soft X-ray SASE line (SASE3). For this purpose, four helical APPLE X undulators with 90 mm period are installed downstream with respect to the planar undulators of the SASE3 undulator line consisting of 21 planar undulators with 68 mm period. In this contribution, the measurement technique, as well as the results of the measurements and tuning of the APPLE X undulators performed at European XFEL are presented.